2019
DOI: 10.1002/jmri.26659
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging biomarkers in musculoskeletal soft tissue tumors: Review of conventional features and focus on nonmorphologic imaging

Abstract: The majority of peripheral musculoskeletal soft tissue masses encountered in routine clinical practice are benign and associated with an excellent prognosis, whereas a small proportion of soft tissue masses are malignant and are associated with higher morbidity and mortality. Owing to the excellent tissue contrast resolution provided, magnetic resonance imaging (MRI) is a primary modality for the diagnostic evaluation of soft tissue masses, particularly for defining the anatomic extent. MRI is also useful for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
0
23
1
Order By: Relevance
“…Although conventional T1-weighted, fluid-sensitive sequences, and static contrast-enhanced imaging remain essential for the assessment of tumor extent and qualitative features, chemical shift imaging, diffusion-weighted imaging (DWI), perfusion imaging, and magnetic resonance spectroscopy (MRS) provide additional information regarding the physiologic and metabolic features of tumors that can be used to help categorize lesions as benign or malignant, and similarly separate viable malignant tissue from areas of posttreatment benign fibrosis. 8,9 Bone Marrow Assessment with Marrow-specific Sequences The characterization of potential bone marrow signal abnormalities often rests on conventional noncontrast spin-echo T1-weighted imaging, 10 whereby marrow-replacing lesions appear as low signal intensity lesions against a background of fatty marrow. Chemical shift imaging with in-phase and opposed-phase imaging offers a method of distinguishing true marrow replacement from signal abnormalities due to edema or hypercellular red marrow.…”
Section: Musculoskeletal Malignanciesmentioning
confidence: 99%
“…Although conventional T1-weighted, fluid-sensitive sequences, and static contrast-enhanced imaging remain essential for the assessment of tumor extent and qualitative features, chemical shift imaging, diffusion-weighted imaging (DWI), perfusion imaging, and magnetic resonance spectroscopy (MRS) provide additional information regarding the physiologic and metabolic features of tumors that can be used to help categorize lesions as benign or malignant, and similarly separate viable malignant tissue from areas of posttreatment benign fibrosis. 8,9 Bone Marrow Assessment with Marrow-specific Sequences The characterization of potential bone marrow signal abnormalities often rests on conventional noncontrast spin-echo T1-weighted imaging, 10 whereby marrow-replacing lesions appear as low signal intensity lesions against a background of fatty marrow. Chemical shift imaging with in-phase and opposed-phase imaging offers a method of distinguishing true marrow replacement from signal abnormalities due to edema or hypercellular red marrow.…”
Section: Musculoskeletal Malignanciesmentioning
confidence: 99%
“…Crombé et al have identified MRI features at 1.5 T such as peritumoral enhancement, the presence of an area compatible with necrosis and heterogeneous signal intensities in T2W images which could be linked to high grade-tumours. One could expect, as previously suggested, that UHF MRI might play a role in sarcoma prognosis analysis and patient outcome assessment [45,46]. Right: ADC map computed from UHF MRI acquisitions and merged on GRE sequence.…”
Section: Discussionmentioning
confidence: 85%
“…The diagnostic accuracy of routine MRI sequences remains less than perfect for the majority of STTs, due to overlapping features, especially after determinate soft tissue masses such as lipoma and ganglia are excluded. A benefit to characterisation has been shown with the use of advanced MRI sequences (DWI, DCE-MRI) [ 38 , 39 ]. There are some STTs that can be diagnosed with high accuracy based on imaging characteristics and location, such as PNSTs (schwannoma and neurofibroma), palmar/plantar fibromatosis, fibromatosis colli, eslatofibroma dorsi, and lipomatosis.…”
Section: Discussionmentioning
confidence: 99%